2016
DOI: 10.1016/j.biortech.2016.01.048
|View full text |Cite
|
Sign up to set email alerts
|

Identification of recalcitrant compounds in a pilot-scale AB system: An adsorption (A) stage followed by a biological (B) stage to treat municipal wastewater

Abstract: This manuscript presents a comparison of the A-stage and B-stage sludges in terms of anaerobic biodegradability and low molecular weight compounds present in the supernatant using Gas Chromatography-Mass Spectrometry (GC-MS). The GC-MS analysis of A-stage and B-stage supernatants identified respectively 43 and 19 organic compounds consisting mainly of aromatics (27.9% and 21%), alcohols (25.6% and 15%) and acids (30.2% and 15%). The methane potential was found to be 349±1 mL CH4/g VS and 238±12 mL CH4/g VS, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Thus, a full-scale HiCS system could potentially achieve an energy recovery of more than twice as high as that of a CAS system. It should be noted that the methane yield from HRAS sludges may differ depending on the type of sludge, wastewater, and anaerobic digestion conditions, and values between 44% and 73% COD methane COD sludge‑fed –1 have been reported. , Digestibility experiments of HiCS sludge should therefore be performed to estimate of the energy recovery potential of the HiCS system under various conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, a full-scale HiCS system could potentially achieve an energy recovery of more than twice as high as that of a CAS system. It should be noted that the methane yield from HRAS sludges may differ depending on the type of sludge, wastewater, and anaerobic digestion conditions, and values between 44% and 73% COD methane COD sludge‑fed –1 have been reported. , Digestibility experiments of HiCS sludge should therefore be performed to estimate of the energy recovery potential of the HiCS system under various conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, sludge from the USAS process is also considered to be a potential raw material for energy recovery. Studies by Trzcinski et al 12 and Meerburg et al 13 suggested that sludge obtained from the A stage achieved a higher methane yield than that from B stage by 1.4–1.9 times during the anaerobic digestion process. However, few studies have focused on the analysis of lipids from USAS sludges.…”
Section: Introductionmentioning
confidence: 99%
“…Anaerobic digestion of sludge obtained from an A-stage process (Asludge) has previously been compared to that of WAS and/or sludge obtained from the B-stage (B-sludge) (Trzcinski et al, 2016;Cagnetta et al, 2017). Notably, WAS and B-sludge are originating from reactors operated at long SRTs, resulting in decreased sludge biodegradability (Bolzonella et al, 2005).…”
Section: Introductionmentioning
confidence: 99%